2017
DOI: 10.1111/ijn.12529
|View full text |Cite
|
Sign up to set email alerts
|

Development of simulation‐based learning programme for improving adherence to time‐out protocol on high‐risk invasive procedures outside of operating room

Abstract: The aim of this study was to develop a simulation-based time-out learning programme targeted to nurses participating in high-risk invasive procedures and to figure out the effects of application of the new programme on acceptance of nurses. This study was performed using a simulation-based learning predesign and postdesign to figure out the effects of implementation of this programme. It was targeted to 48 registered nurses working in the general ward and the emergency department in a tertiary teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As evidenced by this study's participant response to the SET-M question indicating that prebriefing increased their confidence, one can assume both the AL platform and discussion with simulation faculty before the start of the simulation were useful. The time-out method utilized in the intraoperative environment to refocus clinicians’ clinical judgment and patient safety can be useful in a telehealth simulation like the one used in this feasibility study ( Hofman & Lobaton, 2016 ; Jeong et al, 2017 ; Jones, 2019 ; Kuszajewski et al, 2021 ; Sarmasoglu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by this study's participant response to the SET-M question indicating that prebriefing increased their confidence, one can assume both the AL platform and discussion with simulation faculty before the start of the simulation were useful. The time-out method utilized in the intraoperative environment to refocus clinicians’ clinical judgment and patient safety can be useful in a telehealth simulation like the one used in this feasibility study ( Hofman & Lobaton, 2016 ; Jeong et al, 2017 ; Jones, 2019 ; Kuszajewski et al, 2021 ; Sarmasoglu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The generational gap of faculty participants could have played a role in this discrepancy, as Chica and colleagues speak to this barrier in online nursing programs nationwide (Chicca & Shellenbarger, 2018). Realism in the AL platform and cases was also appealing to participants, as has also been seen in many studies that utilized Association of Standardized Patient Educators best practices in the delivery of simulations using SPs (Hofman & Lobaton, 2016;Jeong et al, 2017;Jones, 2019). Participants reported prebriefing and debriefing of the simulation cases to be most helpful, as well as time outs during the simulations both on the SET-M scores and in their focus groups.…”
Section: Perceptions Of Al Cases and Telehealth Simulationsmentioning
confidence: 99%
“…Studies in emergency medicine reveal a gap that could lead to patient harm. Jeong et al 12 developed a time-out protocol for nurses for procedures outside the operating room. In a study by Kelly et al, 7 most ED leaders reported a time-out was warranted when sedating patients.…”
Section: Discussionmentioning
confidence: 99%